An exploratory research of calorimetric and structural shape memory effect characteristics of Cu–Al–Sn alloy - Canbay, Canan Aksu; Karaduman, Oktay; Ünlü, Nihan; Özkul, İskender (Elsevier B.V., 2020)
The ternary CuAlSn alloy was fabricated as cast ingot by arc melting method and the traditional homogenization and fast cooling (quenched in iced-brine water) SMA processes were carried out on small-cut samples of the ingot alloy. Then, the differential thermal and structural EDX, XRD measurements and analyses were made for this monotype alloy samples. The DSC thermograms graphed at different heating/cooling rates revealed the deep endo/exo peaks indicating martensitic phase transitions occurred in the alloy. The alloy's behavior in high temperature region was elicited by DTA results. The thermodynamical parameters such as characteristic phase transformation temperatures, hysteresis, enthalpy and entropy changes, equilibrium temperature were determined either by taking directly from DSC data or by calculations made on them. XRD measurement made in room conditions showed the diffraction patterns belong to the existing martensite phase in the alloy, plus the crystallite size of the alloy was computed by using XRD data. © 2019 Elsevier B.V.
Keywords: Austenite; Cu-Al-Sn shape memory alloy; DSC; DTA; Martensite; Shape memory effect